1996
DOI: 10.1002/(sici)1097-0177(199602)205:2<172::aid-aja8>3.3.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Connexins and E‐cadherin are differentially expressed during trophoblast invasion and placenta differentiation in the rat

Abstract: We have characterized the spatial and temporal expression pattern of six different connexin genes and E-cadherin during trophectoderm development in the rat. During the initial phase of trophoblast invasion at 6 days postcoitum (dpc), the trophoblast expressed E-cadherin but no connexin expression could be observed. With progressing invasion of the polar trophoblast into the maternal decidua, from 7 dpc onwards E-cadherin expression in the ectoplacental cone cells was lost and was now restricted to the extraem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 0 publications
3
26
0
Order By: Relevance
“…Our study demonstrated that E-cadherin protein expression was extremely low or undetectable in secondary trophoblast outgrowth in vitro. Similar results were shown in other mammalian embryos where downregulation of E-cadherin was coincident with the differentiation of TGCs in the rat (Reuss et al 1996), and with the differentiation of non-invasive cytotrophoblast into invasive trophoblast in the human (Coutifaris et al 1991, Floridon et al 2000.…”
Section: Characterisation Of the Secondary Trophoblast Outgrowth Modelsupporting
confidence: 74%
See 1 more Smart Citation
“…Our study demonstrated that E-cadherin protein expression was extremely low or undetectable in secondary trophoblast outgrowth in vitro. Similar results were shown in other mammalian embryos where downregulation of E-cadherin was coincident with the differentiation of TGCs in the rat (Reuss et al 1996), and with the differentiation of non-invasive cytotrophoblast into invasive trophoblast in the human (Coutifaris et al 1991, Floridon et al 2000.…”
Section: Characterisation Of the Secondary Trophoblast Outgrowth Modelsupporting
confidence: 74%
“…Moreover, trophectoderm and TGCs express a 7 integrins (laminin receptors) in the early postimplantation mouse embryo which may facilitate their invasion into the uterine stroma (Sutherland et al 1993, Klaffky et al 2001. On the other hand, E-cadherin, a member of the cadherin family of adhesion molecules, is expressed by embryonic ectoderm, trophectoderm and labyrinthine trophoblast cells, but is absent on TGCs in the rat (Reuss et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…its derivatives Reuss et al, 1996). This expression persists and Cx31 is found in the Jz followed by a coexpression of Cx43 at early midgestation (Kibschull et al, 2005).…”
Section: Exclusive Expression Of Cx31 By Gcsmentioning
confidence: 94%
“…Exposure to Kodak XAR-5 films took place at 80 C with intensifying screens. After exposure, each blot was re-hybridized with a rat actin-specific cDNA probe (Reuss et al 1996) using the same conditions of hybridization.…”
Section: Northern Blot Analysismentioning
confidence: 99%